Influence of duration and frequency of load application on the stress-strain state of the track - M. M. Zheleznov; V. O. Pevzner; V. P. Solov’ev; A. V. Anisin; I. M. Anisina; S. S. Nadezhin; I. V. Tret’yakov (Вестник Научно-исследовательского института железнодорожного транспорта)
Abstract. In 2014–2016 on the Kovdor—Pinozero section of Oktyabrskaya Railway tests were carried out on the impact of cars with axial loads of 245.3 and 264.9 kN on the track in comparison with standard cars with an axial load of 230.5 kN. Test program included trips to five experimental sections of the track with the same construction of the track superstructure, but different parameters of the road bed. Tests carried out on the impact on the track of trains weighing from 2000 to 8000 tons at different axial loads of cars and moving at different speeds made it possible to estimate the dependence of the growth of vertical forces acting on the rail on the duration and frequency of load application. Work on the registration of vertical forces was carried out by the specialists of the Department “Tracks and track facility” of the JSC “VNIIZhT”. On the basis of the results obtained, a mathematical model was developed that describes the effect of increasing the impact of railcars on the track as the load application increases, allowing calculations for various characteristics of the base. In the future, it is planned to use this model to estimate the accumulation of deformations of the track with different characteristics of the base and variants of train load. Obtained results allow stating that the accumulation of track failures depends not only on the level of the axial load and the mass of the train, but also on the duration and frequency of the load application.